Hardware in the Loop Simulation for Soda Can Palletizing Process Applying Ethernet TCP/IP Communication Protocols Based on Unity 3D - Cadena, Mateo (2023)
Technological evolution and the latest advances in science focused on industry have been growing each day; by now, we use terms such as “Industry 4.0”, this has meant innovation at the production level, industrial control, and virtualization of more precise environments. In the present work, Hardware in The Loop (HIL) technique was used for the implementation of a virtual environment of the industrial process of stacking or palletizing soft drink cans using the UNITY GAME ENGINE development platform. In the implementation of the simulation of this process, the greatest number of characteristics and physical limitations of the real process were taken into account, with the purpose of getting a precise virtual environment simulation, so it has the greatest number of details or realism. In this way to implement an Ethernet network that allows control of the simulated process and gives a clear idea of ​​how one of the most important parts works within the production lines of companies.